Sharjah Biennial 15: Thinking Historically in the Present (Sharjah Art Foundation, 2025)
Exhibition catalog. Essay: Hoor AlQasimi, Ahmad Makia. Working group: Tarek Abou El Fatouh, Ute Meta Bauer, Salah M. Hassan, Chika Okeke-Agulu, Octavio Zaya. Contributors: Nadi Abusaada, Maitha Ali, Stephanie Bailey, Billy Fowo, Sharmeen Inayat, Fawz Kabra, Henry Ace Knight, Christopher J. Lee, Ruba Al-Sweel, Cindy Sissokho.
English
Keywords: Biennial catalog; N4390-5098 Visual Arts- Exhibitions; UAE -- Sharjah